he Secret Life of Another Indian Nationalism: Transitions from the Pax Britannica to the Pax Americana - Mayaram, Shail (UK: Cambridge university press, 2022)
Nationalism is among the most influential ideas that has shaped the 'Metamorphoses of the Political' in the long twentieth century. This book focuses on exclusivist Indian nationalism and identifies its distinction from inclusivist nationalism. It highlights shifts in 'another Indian nationalism' over the last two centuries as the geopolitical context has transitioned from the Pax Britannica to the Pax Americana and its war on terror. The books braids the following three strands together: first, a majoritarian nationalist ideology called Hindutva; second, the making of popular history as a precolonial epic is highlighted, depicting the defeat of the last Hindu Emperor by a conquering Muslim Sultan purportedly leading to eight centuries of Hindu enslavement and third, the 'reconversion' of a community by the Visva Hindu Parishad with consequences for Lived Hinduism and Indic civilisation with its complex identities.